Comparative Study of Antigen Detection and Viral Nucleic Acid Assay for Early Detection of Dengue Infection (IAHS Medical Journal, 2022)
Background : Differentiating dengue patients from other acute febrile illness patients is a great challenge among physicians. Thus early and rapid diagnosis of dengue virus infection is of top most importance. The present study was designed to establish an early and rapid diagnosis of dengue virus infection from single serum samples with comparison between two methods-antigen detection by Immunochromatographic test (ICT) and nucleic acid assay by Real time RT –PCR.Materials and methods : This cross sectional study was carried out in the Department of Microbiology, Chittagong Medical College and Chevron Laboratory in Chattogram during the period of January 2012 to December 2012. A total 115 clinically suspected dengue patient of all ages and both sexex from indoor and Out Patient Department (OPD) of Chittagong Medical College Hospital were enrolled in this study.Results : These test were done in 2-7 days of fever. Blood samples from 115 clinically suspected dengue cases had been taken. Among them, NS1 antigen by ICT were found positive in 78(67.8 %) cases and DENV RNA by realtime RT-PCR in 64 (55.7% ) cases. Among 64 dengue PCR positive cases, dengue ICT was found positive in 61 (95.30%) cases & not detectable in 03 (4.65%) cases and in 51 PCR negative cases, 17 were found positive by ICT. The difference in diagnosing dengue by ICT and PCR was found highly significant, p < 0.001. Highest positivity of both test were observed in 2nd to 4th days. In this study, dengue ICT was detected 19 (70%) cases in • 5 days of fever where as PCR was detected only 02 (6.80%) cases. The sensivity , specificity , positive predictive value , negative predictive value of ICT in comparison to PCR were found 95.3% , 66.7%, 78.2 %, 91.9% respectively.Conclusion : In the comparative evaluation, NS1 Antigen was found to be far more sensitive than Real time RT-PCR 1.IAHS Medical Journal Vol 4(2), December 2021; 60-65